PENGARUH ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA PADA PEMILIK UKM SEKTOR MANUFAKTUR GARMIEN DI TANAH ABANG, JAKARTA PUSAT - ., Silviasih; Slamet, Franky; Iskandar, Denny (Ilmiah Manajemen Bisnis, 2016)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  ABSTRACTThe purpose of this study is to determine whether there is influence of market orientationand entrepreneurial orientation on performance in the small and medium scale of garmentmanufacturers in Tanah Abang, Central Jakarta. The population of this study is the owner of thegarment manufacturers in Tanah Abang, Central Jakarta. The Sample in this study was determinedby non probability sampling method. Researcher distributed questionnaires to 100 respondents. Theresults shows that there is an influence of market orientation and entrepreneurial orientation onperformance in small and medium scale of garment manufacturers in Tanah Abang, Central Jakarta.Market orientation provides the ability to understand and meet the today and future customer needswhich also using their ability to provides superior solutions for customers than their competitors.Entrepreneurial orientation can help to identify and respond earlier to market than their competitorsin order to create competitive advantages and achieve better performance. The implications of thisstudy for the garment manufacturers is to increase the knowledge about the factors that affecting theperformance such as market orientation and entrepreneurial orientation which could develop theirinsights and change the views in entrepreneurship.Keywords: small and medium scale enterprises, market orientation, entrepreneurial orientation,performanceÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh orientasi pasar danorientasi kewirausahaan pada kinerja usaha skala kecil dan menengah produsen garmen di TanahAbang, Jakarta Pusat. Populasi penelitian ini adalah pemilik produsen garmen di Tanah Abang,Jakarta Pusat. Sampel dalam penelitian ini ditentukan dengan metode non probability sampling.Peneliti menyebarkan kuesioner kepada 100 responden. Hasil penelitian menunjukkan bahwa adapengaruh orientasi pasar dan orientasi kewirausahaan pada kinerja usaha skala kecil dan menengahprodusen garmen di Tanah Abang, Jakarta Pusat. Orientasi pasar menggambarkan kemampuanuntuk memahami dan memenuhi kebutuhan pelanggan hari ini dan masa depan sekaligus jugamenggunakan kemampuan mereka untuk menyediakan solusi unggul bagi pelanggan dari pesaingmereka. Orientasi kewirausahaan membantu mengidentifikasi dan menanggapi pasar lebih cepatdari pesaing dalam rangka menciptakan keunggulan kompetitif dan mencapai kinerja yang lebihbaik. Implikasi dari penelitian ini untuk produsen garmen adalah untuk meningkatkan pengetahuantentang faktor-faktor yang mempengaruhi kinerja seperti orientasi pasar dan orientasi kewirausahaanyang bisa mengembangkan wawasan mereka dan mengubah pandangan dalam berwirausaha.Kata kunci: usaha kecil dan menengah skala, orientasi pasar, orientasi kewirausahaan, kinerja